The complete mitogenome of the marine bivalve Lutraria rhynchaena Jonas 1844 (Heterodonta: Bivalvia: Mactridae). (2nd January 2016) - Gan, Han Ming; Tan, Mun Hua; Thai, Binh Thanh; Austin, Christopher M.
Abstract: The complete mitochondrial genome of the commercially important snout otter clam Lutraria rhynchaena was obtained from low-coverage shotgun sequencing data on the MiSeq platform. The L. rhynchaena mitogenome has 16, 927 base pairs (69% A + T content) and made up of 12 protein-coding genes, 2 ribosomal subunit genes, 22 transfer RNAs, and a 953 bp non-coding AT-rich region. This is the first mitogenome to be sequenced from the genus Lutraria, and the seventh to be reported for the family Mactridae.